SYNTHESIS OF METAL PHTHALOCYANINE PIGMENT BASED ON NPK AND CALCULATION OF PARTICLE SIZE USING THE DEBYE-SCHERRER EQUATION - Yusupov, Muzafar; Kayumjanov , Odiljon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
This article presents a comprehensive investigation into the chemical composition, structural characteristics, and particle size of a newly synthesized metal phthalocyanine pigment, employing advanced physical and chemical analytical techniques. The research utilizes a novel experimental approach to elucidate the synthesis process. Specifically, the particle size of the metal phthalocyanine pigments was assessed using the Debye-Scherrer equation. The synthesis of high-intensity metal phthalocyanine pigment is thoroughly examined, and a diagrammatic representation of the components constituting the NPK-based metal phthalocyanine pigment is provided.